Development of the pedestrian anger expression inventory. (17th February 2021) - Esmaeli, Saeed; Aghabayk, Kayvan; Abrari Vajari, Mohammad; Stephens, Amanda N.
Abstract: Objective: There has been extensive research into road user behavior, although how pedestrians express their anger has yet to be explored. This is important given the high vulnerability of pedestrians and the additional risks that angry people often undertake. The present study developed a tool to measure one's tendency to engage in aggressive acts while walking: The pedestrian anger expression inventory (PAX). Methods: The survey consisted of 37 items adapted from the Driving Anger Expression Inventory as well as a subset of items from the Pedestrian Behavior Questionnaire. Ten items from the Trait Anger Scale (TAS) questionnaire were also used to assess the general anger tendencies of individuals. A total of 475 participants from Tehran provided complete responses to a questionnaire administered via paper and pencil. Results: A Principal Component Analysis showed a 30-item, 3-factor model describing three ways of expressing anger: 1) Anger Expression-In (internalizing anger), 2) Anger Expression-Out (in the form of aggression), and 3) Adaptive/Constructive Expression (dealing with anger in a constructive way). Hierarchical linear regression showed that trait anger was a significant predictor of pedestrian anger expression, above other demographic variables (age and gender). However, age and gender remained significant predictors of pedestrian anger. As age increased, the tendency to become angry while walking decreased. Male pedestrians were also significantly more likely to express their anger aggressively than female pedestrians. Conclusions: In this study, we developed a questionnaire to measure anger expression in pedestrians, highlighting three broad ways pedestrians deal with their anger (internally, externally, or constructively). This questionnaire was used in Iran and therefore, further research is required to validate these tools among different samples and populations.